2015
DOI: 10.3109/10641955.2015.1060244
|View full text |Cite
|
Sign up to set email alerts
|

Can Platelet Count and Platelet Indices Predict the Risk and the Prognosis of Preeclampsia?

Abstract: We suggest that the increasing platelet turnover in PE causes a decrease in the PC, an increase of MPV value and especially a decrease in PC/MPV ratio pointing that these parameters may play an important role in predicting the risk of PE while they have no role on predicting the severity of PE. According to our findings we can suggest that the patients with these cut-off values of PC and platelet indices, should be carefully followed for the development of PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
61
5
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 15 publications
10
61
5
4
Order By: Relevance
“…Recently, Doğan et al14 observed significantly lower PC and PC/MPV in preeclamptic women compared with the controls. The same study documented significantly higher MPV in preeclamptic women than the control group.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Doğan et al14 observed significantly lower PC and PC/MPV in preeclamptic women compared with the controls. The same study documented significantly higher MPV in preeclamptic women than the control group.…”
Section: Discussionmentioning
confidence: 96%
“…17) A previous report suggested that increased platelet turnover caused by endothelial injury may be one of the reasons for the lower platelet count. 17) Once preeclampsia is complicated by HELLP syndrome, consumption of platelets may increase and promote hemorrhagic tendency.…”
Section: Discussionmentioning
confidence: 99%
“…17) A previous report suggested that increased platelet turnover caused by endothelial injury may be one of the reasons for the lower platelet count. 17) Once preeclampsia is complicated by HELLP syndrome, consumption of platelets may increase and promote hemorrhagic tendency. Although thrombocytopenia is defined as a platelet count less than 100,000/ μl according to the diagnostic standard proposed by Sibai et al, 18) the results of the present study suggest that preeclamptic women should be recognized as being at high risk for bleeding complications by anticoagulant therapy even when preoperative platelet counts are not abnormally low.…”
Section: Discussionmentioning
confidence: 99%
“…En investigaciones previas se ha reportado que los valores son de 78% -90% para la sensibilidad y 83% -86% para la especificidad 10 . En la preeclampsia postparto también se han encontrado que el volumen plaquetario medio es significativamente más alto en las preeclámpticas comparado con las embarazadas normotensas 30 .…”
Section: Discussionunclassified